KARAKTERISTIK COOKIES DARI TEPUNG TERIGU DAN TEPUNG BIJI NANGKA DIMODIFIKASI SECARA ENZIMATIS - Cicilia, Siska; Basuki, Eko; Alamsyah, Ahmad; Yasa, I Wayan Sweca; Dwikasari, Lingga Gita; Suari, Rafika (Journal of Agritechnology and Food Processing, 2021)
This study aims to determine the characteristics of cookies made from wheat with the addition of enzymatically modified jackfruit seed flour. This study used an experimental method with a one-factor Completely Randomized Design (CRD) consisting of 6 levels of the ratio of the use of wheat flour: modified jackfruit seed flour, namely P1=100% : 0%, P2=85% : 15% , P3=70% : 30% , P4=55% : 45% , P5=40% : 60% and P6=25% : 75% with 3 repetitions. Parameters observed included chemical parameters, namely moisture, ash, protein, fat content and organoleptic (color, taste, and texture). The observed data were analyzed for variance (Analysis of Variance) with a significance level of 5%. If there is a significant difference, the Polynomial Orthogonal (MOP) further test for chemical parameters and Duncan's test for organoleptic is carried out. The results showed that the addition of modified jackfruit seed flour with different concentrations gave significantly different effects on all chemical and organoleptic parameters. The higher the addition of modified jackfruit seed flour causes an increase in water content, ash content, protein content, fat content, darker color, denser texture and bitter taste. Treatment with a ratio of 55% flour: 45% modified jackfruit seed flour was the best treatment with 6.94% moisture content; 1.13% ash content; 7.95% protein content and 17.63% fat content.